The Efficiency of Amil Zakat Institutions (LAZ) in Indonesian Islamic Banks: Data Envelopment Analysis Approach - Rofiul Wahyudi, Rofiul Wahyudi; Susetyohadi, Agus (Madania: Jurnal Kajian Keislaman, 2021)
The Amil Zakat Institution (LAZ), based on Islamic bank corporations, has shown a significant role based on the mandate of the 2008 law on the social functions of Islamic banks. However, a performance evaluation is needed to see how efficient the LAZ is in its operations. This study aims to analyze the level of efficiency of the LAZ of Islamic bank corporations in Indonesia. This research method uses a quantitative design with an associative approach. The research subjects were five. Due to limited data, two samples were taken, namely the LAZ of Islamic bank corporations, including Baitulmal Bank Muamalat (BMM) Indonesia and BSM Ummah (BSMU). Efficiency analysis uses the Data Envelopment Analysis (DEA) method of production, asset and intermediation approaches, and the data is tested using Warwick DEA software. The results of this study indicate that all OPZ based on Islamic banks have efficient performance with a value of 100% both on the assumption of Constant Return to Scale (CRS) and Variable Return to Scale (VRS). This means that OPZ from Islamic bank corporations can collect and distribute ZISWA funds. The results of this study also indicate that there are limitations to the research carried out. The researcher recommends further research to add other, more comprehensive approaches, such as intermediation and assets. Lembaga Amil Zakat (LAZ) berbasis korporasi bank syariah telah menunjukkan peran yang signifkaan berdasarkan amanat undang-undang 2008 tentang fungsi sosial bank syariah. Namun, demikian, diperlukan evaluasi kinerja untuk melihat seberapa efisien LAZ tersebut dalam operasionalnya. Tujuan penelitian ini untuk menganalisis tingkat efisiensi LAZ korporasi bank syariah di Indonesia. Metode penelitian ini menggunakan desain kuantitatif dengan pendekatan asosiatif. Subyek penelitian berjumlah lima. Adanya keterbatasan data, diambil dua sampel yakni LAZ korporasi bank syariah meliputi Baitulmal Bank Muamalat (BMM) Indonesia dan BSM Umat (BSMU). Analisis efisiensi menggunakan metode Data Envelopment Analysis (DEA) pendekatan produksi, asset dan intermediasi dan data diuji dengan menggunakan software Warwick DEA. Hasil penelitian ini menunjukkan semua OPZ berbasis bank syariah mempunyai kinerja efisien dengan nilai 100% baik asumsi Constant Return to Scale (CRS) dan Variable Return to Scale (VRS).  Artinya OPZ dari korporasi bank Syariah mempunyai kemampuan  menghimpun dan menyalurkan dana ZISWA. Hasil penelitian ini juga menunjukkan adanya keterbatasan penelitian yang telah dilakukan  Peneliti merekomendasikan penelitian selanjutnya untuk menambahkan pendekatan lain yang lebih komprehensif seperti dalam aspek  intermediasi dan asset.